Research on the Symbiotic Model of Supply Chains Based on the Logistic Expansion Model for E-Commerce Platforms - Zhang, Wei; Fan, Yangming; Yuan, Ye (Sustainability, 2023)
With the development of globalization and technology, e-commerce platforms provide a more convenient shopping experience while also increasing the complexity and difficulty of the supply chain. Managers of e-commerce platform operations need to think about and investigate how to optimize the supply chains of e-commerce platforms, reduce costs and improve efficiency. In this paper, we use the logistic population expansion model to explore the symbiotic relationship among the core populations, key populations and supporting populations within the supply chain ecosystem of e-commerce platforms and the conditions that affect the evolution direction of the symbiotic model. The results show the following: (1) The size of the symbiosis between the three types of populations determines the equilibrium state of the symbiotic evolution of the e-commerce platform supply chain ecosystem. (2) The value of the sum of the symbiotic interaction coefficients between subjects in the supply chain ecosystem of an e-commerce platform determines the result of the symbiotic evolution of the system. (3) The reciprocal symbiosis model can maximize the synergy of the three types of subjects and is the best goal direction for ecosystem evolution. This study can provide a theoretical basis and practical support for the development of e-commerce platform-related enterprises.